INFLUENCE OF LORJUK MUSSEL SHELLS AND PEANUT SHELLS AS CARBURIZER MEDIA IN THE PACK CARBURIZING PROCESS OF AISI 1020 - Achmadi, Achmadi; Widodo, Teguh Dwi; Irawan , Yudy Surya (International Journal of Mechanical Engineering Technologies and Applications, 2025)
AISI 1020 steel is low-carbon steel with a carbon content of 0.20% and good ductility but low hardness. One of the methods to increase the hardness is by infusing carbon. The addition of carbon, called carburizing, was done by heating at a high enough temperature, namely at austenite temperature, in an environment containing active carbon atoms so that the active carbon atoms would diffuse into the steel surface and reach a certain depth. After the diffusion process, a rapid cooling treatment (quenching) is followed to obtain a harder surface, but the center is ductile. The carburizing process requires activation energy to diffuse carbon in the material. Catalysts are one solution to increase activation energy so that the time required during the carburization process is less. The study used carburizer from Lorjuk mussel shells as a catalyst and peanut shell charcoal as a source of activated carbon. The variations used were 0% catalyst/100% charcoal, 10% catalyst/90% charcoal, 20% catalyst/80% charcoal, and 30% catalyst/70%. The results of the study obtained the highest hardness and carbon diffusion values, the smallest corrosion rate obtained in the addition of 30% catalyst, and the lowest hardness in specimens without catalyst.